UPAYA MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA DALAM MATERI MATRIK DENGAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING (GUIDED INQUIRY) - Ade Sri; Nana Rustana (JUMLAHKU: Jurnal Matematika Ilmiah STKIP Muhammadiyah Kuningan, 2021)
The application of scientific-based learning and being able to foster creativity, communication, collaboration and innovation in building a critical mindset is very much needed at this time. This study aims to analyze the improvement of students' mathematical abilities through the Guided Inquiry learning model in class XI students of SMK Negeri 2 Kuningan, West Java, Indonesia. This research method is the Classroom Action Research (CAR) method on the Matrix material. The instruments used are motivation questionnaires, observation sheets, mathematical understanding tests and observation sheets. The results showed that learning motivation and mathematical understanding through the Guided Inquiry learning model increased in each cycle. The students' mathematical understanding ability shown from the test results stated that the average score increased in each cycle and the end of the cycle had reached classical completeness, namely 78%, student and teacher activities during teaching and learning increased in each cycle 46.87% (pre research), 56.25% (Cycle I) and 81.25% (Cycle II)